Identification and detection of Fusarium spp. associated with yellowing disease in black pepper (Piper nigrum L.) using loop-mediated isothermal amplification - Cheong, Shun Hui (2022)
Black pepper (Piper nigrum L.) is an important industrial crop in Malaysia. Yellowing disease caused by the soil-borne Fusarium fungus has caused significant yield loss in black pepper production. This study aims to isolate and characterize Fusarium spp. associated with yellowing disease in Sarawak black pepper using morphological and molecular techniques, and to develop a loop-mediated isothermal amplification (LAMP) assay for rapid detection of F. solani, the dominant Fusarium pathogen in black pepper. Seventy-three isolates of Fusarium fungi were recovered from symptomatic plants sampled from seven districts in Sarawak. Based on morphological and molecular characterization, the identified Fusarium species were F. solani (90.4%), F. oxysporum (5.5%), F. concentricum (2.7%), and F. mangiferae (1.4%). Fusarium species showed distinctive morphological characteristics in mycelial form, colony colour, pigmentation, shape and size of macroconidia and microconidia, types of conidiogenous cells and the presence of chlamydospores. Based on morphological characteristics, F. solani isolates were classified into morphotypes I (20.5%) and II (69.9%). Molecular characterization based on internal transcribed spacer (ITS) and partial translation elongation factor-1 alpha (EF-1α) sequence analysis has indicated high genetic variability among the F. solani isolates. Phylogenetic analysis has divided F. solani isolates into five subclades. The clustering of the subclades was consistent with the morphotype classification. Based on the pathogenicity assay, all four Fusarium species are pathogenic to black pepper. F. solani and F. oxysporum were the most virulent species with 100% disease incidence (DI) eight months after inoculation (MAI). Fusarium-infected black pepper plants showed stunted growth, leaf yellowing, vascular browning, stem necrosis, reduction in leaf number, roots, internode length, and plant fresh and dry weight. Six F. solani-specific LAMP primers were designed from the partial EF-1α sequence. Positive LAMP results were visualized by a colour change from orange to pink and a ladder-like banding pattern on an agarose gel. The amplification temperature was optimized at 65 °C for 60 min. The detection limit of the LAMP assay was 100 pg μL-1 of genomic DNA at 65 °C in 60 min, while the shortest detection time was 30 min using 100 ng μL-1 DNA. The primers were highly specific to F. solani. Digestion of LAMP products using restriction
enzyme BglI has confirmed the amplification specificity. Polymerase chain reaction (PCR) was found to have the same sensitivity and specificity as LAMP. The LAMP assay has a relatively shorter reaction and detection time. Positive detection of F. solani in diseased root samples has indicated that it has the potential to be developed as a detection kit of planting materials for field testing, and useful for disease monitoring and prevention in the field. The results of this study provide essential information to formulate effective disease management strategies for yellowing disease in black pepper.
Keywords: Fusarium wilt; Fusarium solani f. sp. piperis; pathogenicity study; isothermal amplification; rapid diagnosis
Thesis (M.S.) - Universiti Putra Malaysia, 2022.
English.
Keywords: Black pepper (Plant)